Desafios à consolidação do Sistema Único de Assistência Social (Suas): um estudo sobre o Município de Barueri/SP - Leite, Mariana de Oliveira (2015)
This research aims to analyze the challenges for the consolidation of social assistance as a public policy, citizen's right and duty of the state. Its object of study the city of Barueri / SP, and was based on qualitative research through interviews with former managers and other professionals management, as well as reports and documents. The advancement of social assistance policy with the implementation of Suas is undeniable, even considered the political culture in the country that perpetuates the welfare and exerts resistance: the expansion of services and structure, answering level of complexity, a quantitative increase and qualitative human resources, defining responsibilities of entities, the parameters of operation and service, and social control, although incipient, exemplify. However, to think in terms of consolidation of the system, there is still a long way. There are gaps, such as the implementation of social assistance surveillance, social control and the effective participation of users in democratic spaces; the service capacity in social assistance services, yet incompatible with the demand; there are no services considered essential; it is necessary the expansion and training of human resources; the overcoming of culture of charity; networking; among many other measures. The results show that, despite advances, overcoming conservatism and political will are the main ways for the realization of Suas